Biomaterials-based additive manufacturing for customized bioengineering in management of otolaryngology: a comprehensive review - Vyas, Jigar; Shah, Isha; Singh, Sudarshan; Prajapati, Bhupendra G. (Frontiers in Bioengineering and Biotechnology, 2023)
Three-dimensional (3D)/four-dimensional (4D) printing, also known as additive manufacturing or fast prototyping, is a manufacturing technique that uses a digital model to generate a 3D/4D solid product. The usage of biomaterials with 3D/4D printers in the pharma and healthcare industries is gaining significant popularity. 3D printing has mostly been employed in the domain of otolaryngology to build portable anatomical models, personalized patient-centric implants, biologic tissue scaffolds, surgical planning in individuals with challenging conditions, and surgical training. Although identical to 3D printing technology in this application, 4D printing technology comprises a fourth dimension of time. With the use of 4D printing, a printed structure may alter over time under various stimuli. Smart polymeric materials are also generally denoted as bioinks are frequently employed in tissue engineering applications of 3D/4D printing. In general, 4D printing could significantly improve the safety and efficacy of otolaryngology therapies. The use of bioprinting in otolaryngology has an opportunity to transform the treatment of diseases influencing the ear, nose, and throat as well as the field of tissue regeneration. The present review briefs on polymeric material including biomaterials and cells used in the manufacturing of patient centric 3D/4D bio-printed products utilized in management of otolaryngology.